Indigenous-based Resistance: Rethinking the Barambang Katute Indigenous Community's Agrarian Conflict with the Government Through the Indigenous Religion Paradigm - Muammar (LP2M UIN Sunan Kalijaga, 2024)
The government's development narrative often victimizes Indigenous Peoples in Indonesia. Indigenous forests, sacred places for the community, are sought to be legalized for development purposes. This paper is a crisis study of government policies that use the World Religion Paradigm in developing policies toward the Indigenous Peoples of Barambang Katute. This research aims to reveal Indigenous-based resistance from the Barambang Katute Indigenous Community against government and company policies in Sinjai Regency. This article uses the Indigenous Religion Paradigm as its analysis. This research uses a literature study by analyzing written literature on the conflict between Indigenous Peoples and the government in Sinjai Regency. The results of this study mention that resistance in the Barambang Katute Indigenous Community is not only seen from the economic, political, and ecological aspects but also from the socio-religious aspects. The next result framework is written as follows: First, it discusses the history of the causes of agrarian conflicts between indigenous peoples and the government of Sinjai Regency. Second, it discusses the relationship between the Barambang Katute Indigenous Community and nature. Third, it discusses custom-based resistance as the solidarity of indigenous peoples in defending traditional territories. Through the Indigenous Religion Paradigm, we can see that in the efforts to seize the customary forest of Barambang Katute, the government has experienced dynamics and a long journey of conflict. Thus, custom-based resistance is an alternative struggle in defending the existence of customary forests as part of the spirituality of the Barambang Katute Indigenous Community. [Masyarakat Adat di Indonesia seringkali menjadi korban atas narasi pembangunan yang dilakukan oleh pemerintah. Hutan Adat yang merupakan tempat ‘sacred’ bagi masyarakat, diupayakan dilegalkan pemanfaatannya dengan alasan demi kepentingan pembangunan. Tulisan ini merupakan studi krisis terhadap kebijakan pemerintah yang menggunakan paradigma agama dunia dalam melakukan kebijakan pembangunan terhadap Masyarakat Adat Barambang Katute. Penelitian ini bertujuan untuk mengungkapkan resistensi berbasis Adat yang dilakukan oleh Masyarakat Adat Barambang Katute terhadap kebijakan pemerintah dan perusahaan di Kabupaten Sinjai. Secara jelas, artikel ini menggunakan Indigenous Religion Paradigm sebagai analisisnya. Penelitian ini menggunakan studi literatur dengan menganalisis literatur tertulis yang berhubungan dengan konflik Masyarakat Adat dengan pemerintah di Kabupaten Sinjai. Hasil penelitian ini menyebutkan bahwa resistensi dalam Masyarakat Adat Barambang Katute tidak hanya dilihat dari aspek ekonomi, politik dan ekologi melainkan juga dari aspek sosial-keagamaan. Berikutnya kerangka hasil ditulis sebagai berikut: Pertama, membahas tentang sejarah penyebab konflik agraria masyarakat adat dengan pemerintah Kabupaten Sinjai. Kedua, membahas tentang relasi Masyarakat Adat Barambang Katute dengan alam. Ketiga, membahas resistensi berbasis adat sebagai solidaritas masyarakat adat dalam mempertahankan wilayah adat. Melalui Paradigma Agama Leluhur kita dapat melihat upaya perampasan hutan adat Barambang Katute oleh Pemerintah telah mengalami dinamika dan perjalanan konflik yang panjang. Dengan demikian, Resistensi berbasis Adat merupakan alternatif perjuangan dalam mempertahankan eksistensi hutan adat sebagai bagian dari spiritualitas Masyarakat Adat Barambang Katute.]